A Comparison of the Geochemical Characteristics of Ultra-Deep Natural Gas in the Kuqa Foreland and Marine Craton Areas in the Tarim Basin, China - Yu, Cong; Ni, Yunyan; Dai, Jinxing; He, Yuanyuan; Fang, Chenchen; Liao, Fengrong (Frontiers in Earth Science, 2022)
This research analyzed the composition and hydrocarbon isotope geochemical characteristics of ultra-deep natural gas in more than 130 wells in the Tarim Basin. Natural gas in the Kuqa sandstone reservoir is developed as dry gas, with a high methane content (an average of 95.53%) and a low ethane content (an average of only 1.39%). The ultra-deep gas of the marine craton carbonate reservoirs is developed as wet gas. It is mainly composed of methane ranging from 56.1% to 98.8%, with an average content of 76.36% and also contains a small amount of ethane amounting to 6.74%. CO2 and H2S contents of ultra-deep condensate gas in the Central Tarim area are high, with maximum values of 24.2% and 23.1%, respectively. Isotopic characteristics are as follows: δ13C1 values of Kuqa natural gas are distributed between -36 ‰ ~ -25.3 ‰, with an average of -28.2 ‰, δ13C2 values are distributed between -26.2 ‰ ~ -13.8 ‰, with an average of -18.3 ‰. Most gas samples in Kuqa area are developed with the reversal of carbon isotopic series as δ13C2＞δ13C3, and the δ13CO2 values are distributed between -19.5‰ ~ -10.3‰. The δ13C1 values of ultra-deep gas in marine craton carbonate rocks are distributed between - 54.4‰ ~ -33.3‰, with an average of - 42.6‰. δ13C2 values are distributed between - 41.1 ‰ ~ -29.4 ‰, with an average of -33.8 ‰, and δ13CO2 values are distributed between - 28.2 ‰ ~ 0.6 ‰. According to the identification chart, it can be seen that the ultra-deep gas in the sandstone reservoir of the Kuqa foreland is mainly coal-derived gas in the high over-mature stage, and the reversal of carbon isotopic series may be caused by the mixing of natural gas of the same type and different sources. The natural gas in carbonate reservoirs of marine craton is mainly oil-type gas with complex sources, including both kerogen cracking gas and oil cracking gas. CO2 can be formed by organic and inorganic genesis. Inorganic CO2 is most likely to be generated by the dissolution of carbonate rocks under acid formation water.